Chronostructure and circadian rhythms of the parameters of the coagulation system and neurohumoral regulatory systems determining diurnal profile of blood pressure - A.O. Ostapenko; Yu.O. Klitsunova; A.S. Kulbachuk; L.L. Vorontsova (Сучасні медичні технології)
The article is devoted to circadian rhythms of parameters of the hemostatic systems and humoral vasoactive factors determining diurnal profile of blood pressure. Researches indicate the presence of circadian rhythms of activity of autonomic nervous system and renin-angiotensin-aldosterone system in healthy human. Plasma catecholamines maximal activity is observed during the daytime, minimal one at night. Plasma renin activity and aldosterone concentration gradually decreases during the day, reaching its minimum at 4 p.m., followed by increase overnight to a peak at 8 a.m. Angiotensin-converting enzyme diurnal pattern is characterized by monophasic curve with maximal activity in the evening and minimum at night. Physiological features of hemostasis chronobiological characteristics in patients with coronary heart disease are present. All indexes of progressing coagulation and anticoagulation blood system has shown pronounced expressive shift of hypercoagulations in patients in the evening and at night. Fluctuations of insulin and glucose levels during 24 hours are also subject to circadian rhythm, i.e. maximal concentration is observed during the daytime, minimal one at night. Such diurnal rhythms are characteristic for patients without complicated arterial hypertension. However, circadian rhythms disturbances of humoral factors may further violate the circadian profile of blood pressure. It is pointed out that chronotherapy promote further development of the principle of individual treating approach.